2011
DOI: 10.1097/ijg.0b013e3181e08121
|View full text |Cite
|
Sign up to set email alerts
|

Five-year, Multicenter Safety Study of Fixed-combination Latanoprost/Timolol (Xalacom) for Open-angle Glaucoma and Ocular Hypertension

Abstract: After 5 years, more than 70% of participants treated with fixed-combination latanoprost/timolol had no increased iris pigmentation. The fixed combination is safe and well tolerated for long-term treatment in patients with open-angle glaucoma or ocular hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Combination glaucoma drugs enable the possibility of synergistic medical therapies for greater IOP-lowering effect 1215. Although these drugs may offer IOP reduction with increased compliance over instillation of multiple types of medications, there are still disadvantages, including high cost, inconvenience, potential side effects such as corneal epithelial cell damage, and noncompliance.…”
Section: Introductionmentioning
confidence: 99%
“…Combination glaucoma drugs enable the possibility of synergistic medical therapies for greater IOP-lowering effect 1215. Although these drugs may offer IOP reduction with increased compliance over instillation of multiple types of medications, there are still disadvantages, including high cost, inconvenience, potential side effects such as corneal epithelial cell damage, and noncompliance.…”
Section: Introductionmentioning
confidence: 99%
“…Early-phase CTs (phases I/II and III) showed a significant increase over time in the use of biomarkers for patient selection and stratification (including predictive, diagnostic Although 30 of 59 (50.8%) of phase III CTs used secondary surrogate imaging endpoints, we found only 3 of 59 (5.1%) phase III CTs including primary surrogate imaging endpoints: two on retina 16,17 (macular thickness by optical coherence tomography [OCT] and lesion enlargement by fundus autofluorescence) and one on glaucoma 18 (iris color photography). Conversely, phase IV CTs included primary surrogate imaging endpoints in 75 of 275 (27.2%) cases; P < 0.001.…”
Section: Thementioning
confidence: 65%
“…The prevalence of eyelid pigmentation was reported to be between 0 and 61.5% [5, 11, 13, 18, 26]. The racial difference and the duration of PGA administration may explain the differences in the results.…”
Section: Discussionmentioning
confidence: 99%
“…Custer et al [13] retrospectively reviewed PAP in 35 patients using PGAs, and they reported that eyelid pigmentation was not grossly recognized in their case series. In a Swedish study analyzing the safety of a latanoprost/timolol fixed combination, eyelid pigmentation was reported in 6.2% of patients at 60 months of administration [26]. However, Yoshino et al [11] reported that eyelid pigmentation was noticed in 61.5% of Japanese patients who used PGAs for a mean of 67.7 months.…”
Section: Discussionmentioning
confidence: 99%